2014
DOI: 10.1007/s11747-014-0403-8
|View full text |Cite
|
Sign up to set email alerts
|

A new criterion for assessing discriminant validity in variance-based structural equation modeling

Abstract: Discriminant validity assessment has become a generally accepted prerequisite for analyzing relationships between latent variables. For variance-based structural equation modeling, such as partial least squares, the FornellLarcker criterion and the examination of cross-loadings are the dominant approaches for evaluating discriminant validity. By means of a simulation study, we show that these approaches do not reliably detect the lack of discriminant validity in common research situations. We therefore propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

508
14,965
22
486

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20,331 publications
(15,981 citation statements)
references
References 80 publications
508
14,965
22
486
Order By: Relevance
“…Moreover, table 5 shows estimation of HTMT ratio for discrimination validity. It has the threshold of less than 0.85, as suggested by Henseler, Ringle, and Sarstedt (2015). HTMT ratio is an advance statistical technique that helps to assess discriminant validity amongst variables in PLS-SEM, as shown in the above table.…”
Section: Discriminant Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, table 5 shows estimation of HTMT ratio for discrimination validity. It has the threshold of less than 0.85, as suggested by Henseler, Ringle, and Sarstedt (2015). HTMT ratio is an advance statistical technique that helps to assess discriminant validity amongst variables in PLS-SEM, as shown in the above table.…”
Section: Discriminant Validitymentioning
confidence: 99%
“…It has clearly shown that all the variables significantly distinct in their domains. The suggested threshold was considered that all the variables have less than 0.85 coefficients in HTMT ratio for achieving adequate discriminant validity (Henseler et al, 2015). Therefore, it has been achieved appropriately for the current study.…”
Section: Discriminant Validitymentioning
confidence: 99%
“…Table 3 shows that the values of Cronbach's alpha, composite reliability (CR) and rho_A are greater than 0.707 which indicates the acceptable internal reliability of all variables [51]. In addition, the minimum average variance extracted (AVE) value (0.558) surpasses the required cut-off value of 0.5 [52], which reveals an adequate convergent validity level. Additionally, we follow the Fornell and Larcker [53] criterion to assess discriminant validity.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Discriminant validity was assessed by observing that each item loads highest on its designated construct (i.e., cross-loadings) [57] and by ensuring that the square roots of AVEs are greater than the correlation [58]. The heterotrait-monotrait ratio with highest value of 0.682 is below the threshold of 0.850 and provides further support for sufficient discriminant validity [59].…”
Section: Data Analysis and Resultsmentioning
confidence: 99%